La traversée médiatique du simple soldat. À partir de l’œuvre de Bertrand Carrière - Johanne Villeneuve (Revue LISA)
This article deals with the intermediality of the soldier’s experience of war in Normandy, particularly through artistic and non-artistic forms of transmission: from the private gesture of writing embodied in a book, or a Website, to installation art and photography. The starting point for our study is Bertrand Carrière’s installations Jubilee and Caux, both devoted to the death of 1,400 men on the beaches of Dieppe in 1942. Our reading of Carrière’s work leads to some considerations aboutThe Wartime Memories Project,a website collecting memories (stories and photos) of the Great War and the Second World War. Our analysis relies on the relationship between mediation, testimony and cults of the dead. On this basis, the mediation of the soldier’s experience of WWII should be understood as a complex testimony, involving legacy as well as memory and remembrance. It reveals a paradoxical interlacing of anonymous death and the singular experience.